Penerapan Metode Penalized Maximum Likelihood Estimation pada Regresi Multinomial - Erviana; Yayat Karyana (UNISBA Press, 2022)
Abstract. Multinomial regression models are often used to analyze the relationship between categorical response variables that have more than two categories. Parameter estimation in multinomial logistic regression using the Maximum Likelihood Estimation (MLE) method followed by iteration using the Newton-Raphson method. However, sometimes the Maximum Likelihood Estimation (MLE) method cannot be used because it produces an estimator that does not converge, this is due to data separation. To overcome this problem, the Penalized Maximum Likelihood Estimation (PMLE) approach is used. The PMLE method is the result of modifying the probability score function into a penalty probability score. The data used is the 2012 IDHS data for the province of Aceh using data on the desire to have children, after analyzing the data on the desire to have children there are factors that most influence the desire to have children, namely the number of children who are still alive. Abstrak. Model regresi multinomial sering digunakan untuk menganalisis hubungan antara peubah respon yang bersifat kategorik yang memiliki lebih dari dua kategorik. Penduga parameter pada regresi logistik multinomial menggunakan metode Maximum Likelihood Estimation (MLE) yang dilanjutkan dengan iterasi menggunakan metode Newton-Raphson. Namun, terkadang jika menggunakan metode Maximum Likelihood Estimation (MLE) tidak dapat digunakan karena menghasilkan penduga yang tidak konvergen hal ini disebabkan karena adanya pemisahan pada data. Untuk mengatasi pemasalahan ini maka digunakan pendekatan Penalized Maximum Likelihood Estimation (PMLE). Metode PMLE merupakan hasil modifikasi fungsi skor likelihood menjadi skor penalized likelihood. Data yang digunakan adalah data SDKI tahun 2012 untuk wilayah Provinsi Aceh dengan menggunakan data keinginan memiliki anak, setelah dianalisis pada data keinginan memiliki anak terdapat faktor yang paling mempengaruhi keinginan memiliki anak yaitu jumlah anak hidup.